Strategi Branding Berbasis Digital: Membangun Katalog Online untuk Produk Ecoprint Dimdimart of Clothing - Saputra, Mochammad Agung Valintino; Miranda, Ayu; Rosheeda, Amala; Ramadhan, Valenthino; Pratama, Reiyzan Wahyu; Nisa, Aliyatul Khoirun; Maghfiroh, Nuzulul; Anjani, Nindi (Welfare : Jurnal Pengabdian Masyarakat, 2026)
Dimdim Art of Clothing is a creative business that specializes in making environmentally friendly ecoprint products. Our discussion this time focuses on introducing Ecoprint products using an online catalog which functions as an effective digital marketing tool in attracting consumers who care about the environment and sustainable fashion. Through this online catalog, DimDimArt of Clothing hopes to strengthen branding, increase sales, and educate the public about the benefits and beauty of ecoprint products. However, in carrying out the sales business process, DimDimArt of Clothing has several disadvantages, one of which is the limited marketing and promotional media. So far, DimDimArt of Clothing has only used the Whatsapp application, Instagram, website and word of mouth in conducting marketing and promotions. This is considered less than optimal considering the increasingly rapid development of information technology. Therefore, group 5 of sharia business practice internships, Sharia Accounting study program, IAIN helped in upgrading the website and creating a TikTok account for the marketing process. The results of this upgrade have become a medium for introducing products on a large scale.